Cold-induced growth arrest in gilthead sea bream Sparus aurata: metabolic reorganisation and recovery - Sánchez-Nuño, S. (2019)
There are currently no standard diets or practices to counteract or ameliorate the growth arrest and extremely poor feed conversion rates (FCR) in gilthead sea bream Sparus aurata caused by low water temperatures. The present study analysed the effects of reducing dietary lipid content from 18 to 14 % during a temperature fluctuation period. Temperature was gradually reduced from 22 degrees to 14 degrees C over a period of 5 d, and maintained at this low temperature for a further 45 d before gradual recovery over 7 d to 22 degrees C under controlled conditions, avoiding other stressors often present in cage culture conditions. Decreasing dietary lipid content at an elevated temperature (22 degrees C) did not significantly affect the standard growth rate or FCRs of the sea bream, indicating a possibility to reduce the dietary energy during the months before winter. Although cold-induced growth arrest and metabolic depression were unavoidable, a well-formulated, low-lipid diet adequately met the low energy demands at low temperatures. Analysis of plasma metabolites and liver enzyme activities demonstrated a reorganisation of liver metabolism, mainly in fish on a low-lipid diet. Recovery from low temperatures was delayed, with a higher dietary lipid content required for optimal liver condition, and mineral supplementation to maintain osmoregulation and bone formation. Our results provide useful information for fish producers and researchers, suggesting that dietary lipid contents should be reduced to allow fish to better cope with low temperatures, and that improved diets with higher lipid content are required for recovery from low temperatures.